Informatics and Management Science VI - Du, Wenjiang. (Lecture Notes in Electrical Engineering,, 2013)
The International Conference on Informatics and Management Science (IMS) 2012 will be held on November 16-19, 2012, in Chongqing, China, which is organized by Chongqing Normal University, Chongqing University, Shanghai Jiao Tong University, Nanyang Technological University, University of Michigan, Chongqing University of Arts and Sciences, and sponsored by National Natural Science Foundation of China (NSFC). The objective of IMS 2012 is to facilitate an exchange of information on best practices for the latest research advances in a range of areas. Informatics and Management Science contains over 600 contributions to suggest and inspire solutions and methods drawing from multiple disciplines including: ʺ Computer Science ʺ Communications and Electrical Engineering ʺ Management Science ʺ Service Science ʺ Business Intelligence